Consumer Satisfaction of the Tempeh Product’s Pejeruk Abian - Ilhamudin, M.; Masrun, Masrun (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study aims to find out the consumer satisfaction of tempeh products produced by the Pejeruk Abian tempeh industry center in Mataram City. The type of research is descriptive which is used to get an idea of the satisfaction of the tempeh product based on the consumer criteria. This study uses a sample survey method, by choosing the center of Pejeruk Abian’s tempeh industry as the research location. The study population is all tempeh consumers who come to make purchases at the center, or consumers elsewhere who buy Pejeruk Abian tempeh. In determining respondents as data sources in this study, the researcher used a purposive sampling technique. Because the number of members of the research population is not known for sure, the number of research samples is determined to be 100 respondents. To answer the problems raised, the analysis tools used are Consumer Satisfaction Index (IKK) Analysis and Cartesian diagrams, namely consumer evaluations of what they feel and what they want. This model measures the difference between what is perceived and what consumers want. The results of the study showed that consumers were satisfied with the attributes of the Pejeruk Abian tempeh product. This is shown by the CSI value at 1.06, which means that the attributes of the tempeh product are in accordance with consumer wishes.